On the Energy Efficiency of Indoor Air Conditioning - S. N. Osipov; A. V. Zakharenko; E. M. Shirokova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The increase of average outdoor temperatures and their fluctuations over the past 20 years (as evidenced by the records of summer temperatures in our country) has significantly increased the need for air conditioning premises where people are present for a long time, especially when they are crowded (shops, entertainment halls, classrooms, etc.). The air conditioning process is quite energy-intensive, but the growth of well-being in many republics of the former USSR, as well as the increasing complexity of the physiological adaptation of the human body to rising outdoor temperatures make it possible (and at the same time necessary) to implement these systems on a large scale. It is important to take into account that electricity prices are currently maintained at a high level for homeowners, and in the coming years the prices will only grow. Therefore, the development of new ways of significant increase of the energy efficiency of the indoor air conditioning process is of a great interest. One of these methods is the use of laminar (or close to them) moving layers of conditioned air in a limited area of work or rest of people. Such a zone, about 1.0‒1.2 m height from a floor in each apartment is, e.g., living rooms (bedroom) in which standard temperature conditions are created by means of simple air supplying and air intake devices. In the case of sedentary work of people, the height of such a zone of conditioned air should be increased to 1.3‒1.5 m. It has already been established that the use of laminar (or close to them) air flows allows to reduce the power consumption by two or more times due to significantly reduced heat exchange with the surrounding heated surfaces. Besides, the simplicity of such systems ought to be noted. In particular, in conditions of modern systems of control and management of air conditioning, the "duties" of consumers include only the installation on the control device of the initial data relating directly to the required parameters of the microclimate. At the same time, it should be noted that there is currently no complete scientific and technical description of aerodynamic and heat exchange processes in the air conditioning zone. Even in modern conditions for countries with a sharply continental climate (Russia, Kazakhstan, etc.), the problem is the choice of the type of air conditioner for its effective use in hot periods of summer. In general, it can be noted that all the problems of energy-efficient use of air conditioners must find a comprehensive solution.